2016
DOI: 10.1002/cjce.22635
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of bioreactor operating conditions using computational fluid dynamics techniques

Abstract: High hydraulic retention times are commonly used in bioreactors, as they provide greater contact time between substrate and biomass. These reactors also operate at low flow rates to minimize damage to the biomass due to shear stress and drag. However, a high flow rate provides greater mixing, and thus the optimal operation condition is difficult to estimate. In this study, the effect of different flow rates on the behaviour of the phases in an anaerobic sequencing batch bioreactor is evaluated numerically. Flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 19 publications
(27 reference statements)
1
6
0
Order By: Relevance
“…The anaerobic digestion occurs at the mesophilic regime at 37°C. As previously said, it is assumed that the sugarcane vinasse is Newtonian [6] and the fluid is isothermal and incompressible. The rheological properties of the medium are related to the total solid (TS) content of the substrates.…”
Section: Theoretical Model 21 Assumptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The anaerobic digestion occurs at the mesophilic regime at 37°C. As previously said, it is assumed that the sugarcane vinasse is Newtonian [6] and the fluid is isothermal and incompressible. The rheological properties of the medium are related to the total solid (TS) content of the substrates.…”
Section: Theoretical Model 21 Assumptionsmentioning
confidence: 99%
“…Viscosity is the term to express the resistance of a fluid to flow and motion. It is assumed that the sugarcane vinasse is Newtonian [6]. In order to model the flows within a digester, it is therefore necessary to know both its technical characteristics (geometry, stirring mode) and the fluid properties.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Wongnoi et al [36] modified a GLSS using a model-based design approach, obtaining a more efficient structure that reduced the premature exit of solids from the reactor. Other studies using the technique have revealed, for instance, the presence of a discontinuity in the flow within the reaction zone [37] or that the water inlet velocity directly relates to the height of the sludge layer [38]. However, there is an information gap on the relationship between IDS configurations and their potential for granule production.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, high viscosity of lignocellulose slurry constrains mixing results, and the impeller is the main structure that determines the mixing effect and power consumption. Many impeller designs are mainly focused on optimization of height‐to‐tank diameter ratio, impeller types such as energy efficiency on pitched blades, helical ribbon impeller and Rushton and others, and operation conditions like critical stirring speed are investigated . Ahead of developing an appropriate reactor, the rheological properties of the enzymatic hydrolysis slurry should be studied .…”
Section: Introductionmentioning
confidence: 99%
“…Many impeller designs are mainly focused on optimization of height-to-tank diameter ratio, [22] impeller types such as energy efficiency on pitched blades, [23] helical ribbon impeller and Rushton [24] and others, [25] and operation conditions like critical stirring speed are investigated. [26][27][28] Ahead of developing an appropriate reactor, the rheological properties of the enzymatic hydrolysis slurry should be studied. [29] Direct measurement by rheometer and indirect representation by model are two common approaches to characterize the rheology of liquid.…”
Section: Introductionmentioning
confidence: 99%